2016
DOI: 10.3389/fpsyg.2015.02022
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of the Integration of Intention and Outcome in Harmful and Helpful Moral Judgment

Abstract: The ability to integrate the moral intention information with the outcome of an action plays a crucial role in mature moral judgment. Functional magnetic resonance imaging (fMRI) studies implicated that both prefrontal and temporo-parietal cortices are involved in moral intention and outcome processing. Here, we used the event-related potentials (ERPs) technique to investigate the temporal dynamics of the processing of the integration between intention and outcome information in harmful and helpful moral judgm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
2
11
1
Order By: Relevance
“…These results suggest that regardless of treatment type (i.e., generous or greedy), intention always has an amplified impact on generalized reciprocity. Beyond that, such influence of intention on generalized reciprocity provides supporting evidence for previous findings in many other fields, including moral judgment (e.g., Cushman et al, 2013;Gan et al, 2016) and direct reciprocity (e.g., Vaish et al, 2018), and extends our knowledge of the effect of prior intention to generalized reciprocal behaviors.…”
Section: Discussionsupporting
confidence: 82%
“…These results suggest that regardless of treatment type (i.e., generous or greedy), intention always has an amplified impact on generalized reciprocity. Beyond that, such influence of intention on generalized reciprocity provides supporting evidence for previous findings in many other fields, including moral judgment (e.g., Cushman et al, 2013;Gan et al, 2016) and direct reciprocity (e.g., Vaish et al, 2018), and extends our knowledge of the effect of prior intention to generalized reciprocal behaviors.…”
Section: Discussionsupporting
confidence: 82%
“…As a means to answer these questions, we can capitalize on findings regarding the electrocortical processes related to the perception of moral content. These have been investigated by studies using both pictorial and text stimuli (Lahat et al ., 2013; Yoder and Decety, 2014; Cowell and Decety, 2015b; Gan et al ., 2016; Gui et al ., 2016). These studies show that moral content is detected early, and processed throughout several stages.…”
Section: Introductionmentioning
confidence: 99%
“…Recent brain imaging and lesion studies have sought to reveal the brain regions underlying intent-based moral judgements. Consistent with the preferential lateralization of language to the left hemisphere, moral judgement tasks in which moral vignettes are presented linguistically have revealed that various regions of the left hemisphere seem to be involved in intent-based moral judgement, including but not limited to the left medial prefrontal cortex, left temporal parietal junction and left cingulate [ 4 , 7 9 ].…”
Section: Introductionmentioning
confidence: 84%